Implementation of The Policy On Periodic Testing of Motor Vehicles (Kir Test) at The Technical Implementation Unit For Motor Vehicle Testing of The Sekadau District Transportation Service - Weli Bertus (Journal of Social and Policy Issues, 2025)
This research is entitled The Implementation of Regular Vehicle Inspection (RVI) at the Technical Implementation Unit for Motor Vehicle Inspection, Department of Transportation, Sekadau Regency. Regular Vehicle Inspection aims to check, examine, and inspect all vehicles that must undergo regular inspection. The inspection examines the functional parts of a vehicle within the component system and the technical dimensions of motor vehicles, both based on applicable regulations and objective technical requirements. This research is conducted to illustrate and analyze factors (communication, resources, disposition, and bureaucracy system) in implementing the RVI policy in the Technical Implementation Unit for Motor Vehicle Inspection, Department of Transportation, Sekadau Regency. The research was a descriptive-based design with a qualitative approach. The results indicate that the communication factor of the policy implementation has not run effectively. This was evident from the communication process or information transfer, which is still considered unclear. In the disposition (attitude) factor, the research revealed less maximal results. The same result was also delivered in the resource factors, which the personnel of the inspection is lacking. Additionally, the information availability and authority are not yet optimal. Based on these findings, communication should be undertaken effectively and efficiently. In addition, the disposition or attitude of the Technical Implementing Unit should be created (formed). Finally, competent human resources should be made available, for example, by supplying additional personnel, improving and maintaining inspection tools and supporting facilities, and sticking to the SOP in implementing the RVI policy.